Analisis Kinerja Pemerintah atas Indeks Ketahanan Pangan Berdasarkan Kebijakan Fiskal dalam Ekonomi Pertanian pada Kabupaten/Kota di Kawasan Teluk Tomini - Machieu, Siti Rahmatia; Akib, Fitri Hadi Yulia; Mukhtar, Muhammad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The objectives of this study are: (1) to analyze the trend of government performance on the Food Security Index (FSI), and (2) to analyze the influence of fiscal policy in the agricultural economy (general allocation fund (GAF)s, special allocation funds (SAF), and deconcentration funds in the agricultural sector (DF)) on government performance related to the Food Security Index. This study employs a quantitative approach using secondary data from 17 regencies/cities over 5-year period (2020–2024). Data were analyzed using descriptive trend analysis and multiple panel data regression. The findings reveal that (1) the government’s performance on the Food Security Index is relatively good, although the index dynamics vary among provinces in the Tomini Bay region. Central Sulawesi recorded an average FSI growth of -1.21%, North Sulawesi showed an average growth of 0.34%, while Gorontalo Province achieved the highest and relatively stable average growth of 0.43%. (2) The general allocation fund, special allocation fund, and deconcentration fund in the agricultural sector jointly have a significant effect on the Food Security Index of regencies/cities in the Tomini Bay region, with a coefficient of determination (R²) of 22.2373%, while the remaining 77.7627% is explained by other variables. Partially, the general allocation fund has a positive but insignificant effect on the Food Security Index, while both the special allocation fund and deconcentration fund in the agricultural sector have a positive and significant effect on the index.